Characteristics of carbon reinforced concrete Single-sided short time textile pull-out (SPO) Experiments - Amer, Zuhair Mansour (Journal of engineering sciences and information technology, 2022)
Carbon reinforced concrete (CRC) is an innovative alternative to steel reinforced concrete. More and more buildings are being constructed or renewed and strengthened with CRC. Carbon reinforced concrete development is associated with long-term growth in many industries. In addition to the construction industry, the chemical, mechanical engineering and textile industries in particular benefit from the widespread impact. When carbon reinforced concrete is used in the field of repair and strengthening, it increases the bearing elements’ capacities without notable increasing the element’s thickness, therefore it does not lead to an increase in the weight of the structure, nor to a change in its original size or shape. The increasing use of carbon reinforced concrete mainly requires knowledge of its constituent materials’ properties in addition to the behavior of the composite, especially under tensile stress, including the bond between fibres and concrete. Detailed knowledge is particularly required in low concrete age is required if the element strengthened with CRC is to be loaded again as soon as possible. The data available on this is still comparatively incomplete. So, it is often necessary to rely on experiment to determine these properties. Within the framework of this research, tests were performed on carbon concrete with ages of four, five, seven and ten days to determine the bond properties of CRC under tensile stress. The test results were then evaluated and interpreted, then we finally present the resultant material properties of textile concrete used at a young age. As expected, the force corresponding to the slip value of 1.5 mm increases with increasing age of the sample and is expected to reach the value 5552 N at the age of 28 days. In addition, with the increase in the sample age, the value of the spacing between cracks decreases and the value of the coherence field length decreases as well. In this case, the behavior of carbon-reinforced concrete is similar to that of steel-reinforced concrete.